1989
DOI: 10.1002/jlac.198919890243
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Antamanide

Abstract: The conformation of the cyclic decapeptide antamanide (1) in CDCl3 solution was determined by means of NMR‐spectroscopic methods. Distances obtained from 40 negative NOE values at 500 MHz at low temperature were used as constraints in calculations with the GROMOS molecular dynamics program package to elucidate the most stable backbone conformation in solution. It turned out that there is a fast conformational equilibrium between up to four conformations which differ in a flip about φ and ψ around the two amide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 56 publications
3
36
0
Order By: Relevance
“…A more recent NMR study of antamanide, combined with restrained MD simulations (Kessler et al, 1988(Kessler et al, , 1989, suggested the presence of two or four different structures in chloroform, one being essentially identical to the X-ray structure (Karle et al, 1979). The rate of this process has however not been determined.…”
Section: Application To Antamanidementioning
confidence: 97%
“…A more recent NMR study of antamanide, combined with restrained MD simulations (Kessler et al, 1988(Kessler et al, , 1989, suggested the presence of two or four different structures in chloroform, one being essentially identical to the X-ray structure (Karle et al, 1979). The rate of this process has however not been determined.…”
Section: Application To Antamanidementioning
confidence: 97%
“…The packing of the Phe side chain over Pro residue was observed, e.g. for antamanide [46], and the mechanism of aromatic-proline CH/π interactions was studied recently [47].…”
Section: Resultsmentioning
confidence: 99%
“…Antamanide is a cyclic decapeptide for which experimentally measured 3 J HNÀH a -values are available (Kessler et al, 1989). Previous studies using instantaneous restraining have found no single conformation which could explain the 3 J-values measured (Kessler et al, 1988(Kessler et al, , 1989Bru¨schweiler et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies using instantaneous restraining have found no single conformation which could explain the 3 J-values measured (Kessler et al, 1988(Kessler et al, , 1989Bru¨schweiler et al, 1991). It was previously used to test J-value restraining methodology (Torda et al, 1993;Scott et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation